1983
DOI: 10.1111/j.1365-2125.1983.tb02178.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukaemia: a relationship between intracellular 6‐ mercaptopurine metabolites and neutropenia.

Abstract: 1 6-Mercaptopurine is extensively used in the treatment of childhood lymphoblastic leukaemia to prolong the duration of remission achieved with other drugs. The response to remission maintenance therapy varies widely. 2 We investigated the relationship between red blood cell 6-thioguanine nucleotide, a metabolite of 6-mercaptopurine, and myelosuppression in 22 children with acute lymphoblastic leukaemia in remission. The peripheral neutrophil count was used as an index of myelosuppression. 3 6-Mercaptopurine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(62 citation statements)
references
References 3 publications
4
57
1
Order By: Relevance
“…Higher concentrations of 6-thioguanine nucleotides have been reported in patients with leukopenia [28,29]. For this reason, a baseline assessment of thiopurine methyltransferase activity (phenotype) or genotype may be clinically useful to "tailor" the drug dose in order to reduce the frequency of leukopenia.…”
Section: Azathioprine/6-mercaptopurine: Pharmacogenetics and Therapeumentioning
confidence: 99%
“…Higher concentrations of 6-thioguanine nucleotides have been reported in patients with leukopenia [28,29]. For this reason, a baseline assessment of thiopurine methyltransferase activity (phenotype) or genotype may be clinically useful to "tailor" the drug dose in order to reduce the frequency of leukopenia.…”
Section: Azathioprine/6-mercaptopurine: Pharmacogenetics and Therapeumentioning
confidence: 99%
“…Research on the clinical utility and interpretation of 6-MP metabolite concentrations and TPMT activity measurements was initiated in childhood acute lymphoblastic leukemia [26,35,36]. Subsequently, the relationship between 6-TGN, TPMT, and thiopurine safety and efficacy was examined in pediatric IBD patients.…”
Section: Role Of Metabolite Monitoring In Optimizing Immunomodulator mentioning
confidence: 99%
“…1). Since these metabolites are critical for the therapeutic effect of thiopurines, 6-TGN concentrations have been used as an index of the therapeutic and toxic effects of these drugs [23][24][25]. For example, in children taking identical doses of 6-MP there are wide interindividual variations in RBC 6-TGN concentrations [23], and high concentrations of 6-TGNs are associated with profound bone-marrow suppression, the primary life-threatening thiopurine-induced toxicity [23,25].…”
Section: Tpmt Pharmacogenomics: Clinical Consequencesmentioning
confidence: 99%
“…Since these metabolites are critical for the therapeutic effect of thiopurines, 6-TGN concentrations have been used as an index of the therapeutic and toxic effects of these drugs [23][24][25]. For example, in children taking identical doses of 6-MP there are wide interindividual variations in RBC 6-TGN concentrations [23], and high concentrations of 6-TGNs are associated with profound bone-marrow suppression, the primary life-threatening thiopurine-induced toxicity [23,25]. Clinical studies have demonstrated that genetically determined levels of RBC TPMT activity are inversely correlated with RBC 6-TGN concentrations [23,26,27], supporting the hypothesis that an inherited decrease in TPMT activity might shift the balance among thiopurine metabolic pathways toward the formation of 6-TGNs.…”
Section: Tpmt Pharmacogenomics: Clinical Consequencesmentioning
confidence: 99%